Electron transport in dense degenerate plasmas - Filippov, AV (Journal of physics. Conference series, 2020)
Within a unified approach, a method for calculating the tensors of electrical conductivity, the Seebeck coefficient and thermal conductivity of a nonideal plasma in a magnetic field were considered. Under this unified approach the kinetic coefficients are calculated together with the equation of state for a nonideal plasma within the framework of a quasi-chemical model. Various methods for determining the Coulomb logarithm in the kinetic theory of transport and various options for choosing the boundary value of the wave number of electrons are considered. The scattering of electrons by ions using the phase shift method has been considered and the appearance of values of the Coulomb logarithm less than unity are demonstrated. Electron scattering by the phase shift method is considered using the Buckingham potential which permits to describe the Ramsauer minimum in the transport cross section for electron scattering by noble gas atoms.